PERFORMAN “ITIK CILI” (PERSILANGAN ITIK PEKING X ITIK BALI) UMUR 1-9 MINGGU YANG DIBERI RANSUM KOMERSIAL DAN RANSUM BUATAN DIBANDINGKAN ITIK BALI - Agus Arik Ambara; I N. Suparta; I M. Suasta (Animal Science Study Program, Faculty of Animal Husbandry, Udayana University, 2013)
This study aims to determine the level of growth, carcass production and conversion ransum